Konsep Supervisi Klinis Kolaboratif dalam Perspektif Kajian Islam untuk Peningkatan Profesionalisme Guru di Era Revolusi Industri 4.0 - Riduan, Riduan; Ramdhan, Tri wahyudi (Edukais : Jurnal Pemikiran Keislaman, 2024)
This study aims to explore the implementation of collaborative clinical supervision as a strategy to enhance teacher professionalism in madrasahs in the era of the Fourth Industrial Revolution. Collaborative clinical supervision is seen as an approach that can help teachers develop pedagogical and technological skills to improve teaching quality, while also enhancing classroom management. In the context of madrasahs, which have unique challenges and characteristics, this approach focuses on fostering more intensive interaction between teachers and supervisors through observation, reflection, and constructive feedback. This research employs a qualitative approach using a case study method at MTs Negeri 1 Paser. Data were collected through in-depth interviews, direct observations, and documentation related to the implementation of clinical supervision. The results indicate that collaborative clinical supervision significantly contributes to improving teachers' competencies, both in terms of pedagogical skills and their ability to use technology to support more effective and inclusive learning processes. However, challenges related to limited time, resources, and supervisors' understanding of effective clinical supervision techniques were identified. Therefore, this study suggests the need for further training for supervisors and increased collaboration among stakeholders to maximize the benefits of clinical supervision in madrasahs.